2017
DOI: 10.1200/jco.2016.71.7066
|View full text |Cite
|
Sign up to set email alerts
|

Financial Burden in Survivors of Childhood Cancer: A Report From the Childhood Cancer Survivor Study

Abstract: Purpose Survivors of childhood cancer may experience financial burden as a result of health care costs, particularly because these patients often require long-term medical care. We sought to evaluate the prevalence of financial burden and identify associations between a higher percentage of income spent on out-of-pocket medical costs (≥ 10% of annual income) and issues related to financial burden (jeopardizing care or changing lifestyle) among survivors of childhood cancer and a sibling comparison group. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…Numerous studies have documented that adult survivors of childhood cancer are at risk for reduced educational attainment, increased financial burden, underemployment, dependent living status, and limited health insurance coverage . Consistent with observations from the general population, SES (specifically, low educational attainment and household income) is directly associated with an increased risk of noncancer‐related mortality among survivors …”
Section: Socioeconomic and Psychosocial Factorsmentioning
confidence: 77%
“…Numerous studies have documented that adult survivors of childhood cancer are at risk for reduced educational attainment, increased financial burden, underemployment, dependent living status, and limited health insurance coverage . Consistent with observations from the general population, SES (specifically, low educational attainment and household income) is directly associated with an increased risk of noncancer‐related mortality among survivors …”
Section: Socioeconomic and Psychosocial Factorsmentioning
confidence: 77%
“…c 2018 Wiley Periodicals, Inc. 1 of 7 wileyonlinelibrary.com/journal/pbc https://doi.org/10.1002/pbc.27587 F I G U R E 1 Financial burden among survivors of childhood cancer and siblings. OOP, out of pocket 18 vocation opportunities. 11,12 These limitations in turn have reduced their access to employer-based insurance.…”
mentioning
confidence: 99%
“…Nipp et al reporting on patients from the CCSS, highlighted the relationship between high OOP expenses and decisions to seek care. 18 Spending levels of 10% or more of household income on OOP expenses were significantly associated with all of the following: problems paying bills, deferring care, or skipping a test, treatment, or follow-up ( Figure 1). 18 Among those who are employed and insured, another consequence of chronic health conditions after cancer has been a reluctance to change jobs for fear of losing health insurance, known as job lock.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These effects may have very real consequences for survivors' long‐term financial outlook and access to care. Compared with age‐matched peers and siblings, YA survivors report lower income and net worth, and they are more likely to be underemployed or unemployed, lack insurance coverage or be covered by Medicaid, have debt, and declare bankruptcy . A recent analysis found that YA survivors also are more likely than their siblings to experience “job lock,” in which they stay in a job to maintain employer‐sponsored medical coverage .…”
Section: Introductionmentioning
confidence: 99%